Prevalencia de hematuria enzoótica bovina en el cantón Marcabelí - Balarezo Balarezo, Wilson Renè (2011)
The present investigation was carried out in the Marcabelí corner, from the 27 of August to the 16 of October of year 2010, with the purpose of determining by means of the method of reactive strips the enzoótica presence of hematuria in the existing bovines in this corner. The following objectives considered: 1. To determine the bovine presence of hematuria enzoótica, by means of reactive strips in the cattle ranches of the Marcabelí corner. to 2.Determinar the bovine percentage of hematuria enzoótica according to the race, sex, age and origin of the animals. In order to carry out east work in vestigo a total of 400 animals in the different cattle ranches from the corner, during a lapse of 51 days. The animals that investigate rum came from the Marcabelí parishes and the Talent, Small farms. The obtained results determined that if exists the presence of Hematuria Enzoótica in the existing bovines in the Marcabelí corner.